2007
DOI: 10.1021/ef0600558
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Emission Parameters of Biodiesel Fuels Obtained from Canola, Hazelnut, and Waste Cooking Oils

Abstract: In this study, usage of methyl ester obtained from waste cooking oil (WCOME), hazelnut oil (HOME), and canola oil (COME) is examined as an experimental material. A reactor was designed and installed for production of methyl ester from these kinds of oil. Physical and chemical properties of methyl esters were determined in the laboratory. The methyl esters were tested in a turbocharged diesel engine with four cylinders and direct injection. The results were compared with No. 2 diesel fuel. The comparison of emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 30 publications
0
37
0
2
Order By: Relevance
“…Diante do grande interesse no uso de combustíveis menos poluentes, sem que haja redução significativa no desempenho dos motores, vários trabalhos têm sido desenvolvidos com motores diesel para uso veicular, com o objetivo de verificar o desempenho desses motores e as suas emissões de gases quando movidos por diferentes combustíveis (Dwivedi et al, 2011;Brijesh & Sreedhara, 2013;Ballesteros et al, 2014). É comum que o biodiesel misturado no diesel mineral reduza a emissão de hidrocarbonetos e óxido de carbono, bem como a densidade de fumaça (Koçak et al, 2007;Buyukkaya, 2010), e aumente as emissões de óxido de nitrogênio, em comparação ao diesel mineral (Canakci, 2007;Sahoo et al, 2009). Além disso, o uso de maiores proporções de biodiesel no diesel mineral também tem implicações econômicas, uma vez que o biodiesel é mais caro e sua disponibilidade ainda é pequena.…”
Section: Introductionunclassified
“…Diante do grande interesse no uso de combustíveis menos poluentes, sem que haja redução significativa no desempenho dos motores, vários trabalhos têm sido desenvolvidos com motores diesel para uso veicular, com o objetivo de verificar o desempenho desses motores e as suas emissões de gases quando movidos por diferentes combustíveis (Dwivedi et al, 2011;Brijesh & Sreedhara, 2013;Ballesteros et al, 2014). É comum que o biodiesel misturado no diesel mineral reduza a emissão de hidrocarbonetos e óxido de carbono, bem como a densidade de fumaça (Koçak et al, 2007;Buyukkaya, 2010), e aumente as emissões de óxido de nitrogênio, em comparação ao diesel mineral (Canakci, 2007;Sahoo et al, 2009). Além disso, o uso de maiores proporções de biodiesel no diesel mineral também tem implicações econômicas, uma vez que o biodiesel é mais caro e sua disponibilidade ainda é pequena.…”
Section: Introductionunclassified
“…Published experiments using WCO biodiesel are generally in line with these trends [17][18][19][20]. Di et al [21] observed a decrease in total hydrocarbon (THC) emissions in blends of WCO biodiesel with ultralow sulfur diesel (ULSD), with the greatest reductions (50%) achieved with pure biodiesel.…”
Section: Introductionmentioning
confidence: 72%
“…Ambient conditions also varied more during the mower tests, which were conducted outdoors. Temperatures during these tests ranged from [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] • C and humidity from 23-73 grains/lb dry air. Even so, ANOVA regression indicated no significant effect for ambient temperature on emission results.…”
Section: Mower Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies [8,17,18,23] have compared CO 2 emissions from biodiesel from multiple feedstocks using the same engine and testing protocol, using chassis or dyno testing. None involved on-road testing.…”
Section: Introductionmentioning
confidence: 99%